Studi Fenomenologi Pemaknaan Masyarakat Terhadap Nilai Filosofi Arca Manusia Peninggalan Zaman Batu di Kabupaten Lahat - Okta Riadi; Desy Misnawati; Fathur Rahman (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Lahat Regency is dubbed as the land of 1000 megaliths, because there are more than 1000 megalith findings registered in the Indonesian muri record. This study aims to determine the meaning of the Simpur Village community on the philosophical value of human statues, namely the results of historical relics in the megalithic era in Lahat Regency. This statue depicts the figure of a leader, who is presented with a strong figure having a head that is slightly protruding forward. This study uses a qualitative descriptive research approach. And this research uses phenomenological studies with data collection techniques in the form of literature studies, interviews, and documentation techniques. This study aims to determine the meaning of the Simpur Village community on the philosophical value of human statues in Simpur Village, Lahat Regency.